2002
DOI: 10.1099/00221287-148-3-643
|View full text |Cite
|
Sign up to set email alerts
|

The positive activator of cephamycin C and clavulanic acid production in Streptomyces clavuligerus is mistranslated in a bldA mutant The GenBank accession number for the sequence reported in this paper is AF436078.

Abstract: In Streptomyces coelicolor bldA encodes the principal leucyl tRNA for translation of UUA codons and controls pigmented antibiotic production by the presence of TTA codons in the genes encoding the pathway-specific activators of actinorhodin and undecylprodigiosin biosynthesis. In Streptomyces clavuligerus the gene encoding the pathway-specific activator of both cephamycin C and clavulanic acid production, ccaR, also contains a TTA codon and was expected to exhibit bldA-dependence. A cloned S. clavuligerus DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 58 publications
1
46
0
Order By: Relevance
“…For actII-orfIV, it has been shown that replacement of the TTA codon by an alternative leucine codon relieves its dependence on bldA and thus allows actinorhodin biosynthesis in bldA mutants (5); comparable results have been obtained after mutagenesis of TTA codons in several antibiotic resistance genes (12). However, at least in some contexts and under certain nutritional conditions, TTA triplets are mistranslated and can provide active gene products in bldA mutants (6,12,18). The target gene (or genes) and corresponding TTA codon underlying the aerial mycelium defect in bldA mutants have not been identified.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…For actII-orfIV, it has been shown that replacement of the TTA codon by an alternative leucine codon relieves its dependence on bldA and thus allows actinorhodin biosynthesis in bldA mutants (5); comparable results have been obtained after mutagenesis of TTA codons in several antibiotic resistance genes (12). However, at least in some contexts and under certain nutritional conditions, TTA triplets are mistranslated and can provide active gene products in bldA mutants (6,12,18). The target gene (or genes) and corresponding TTA codon underlying the aerial mycelium defect in bldA mutants have not been identified.…”
mentioning
confidence: 51%
“…We have presented evidence suggesting that adpA transcription is activated during aerial hypha formation and that its TTA triplet is required for aerial mycelium formation. However, we reemphasize that these and other studies of bldA do not prove that the activity of a specific tRNA reflects a bona fida regulatory system (18) or that it is necessarily peculiar to developmental systems in Streptomyces. Interestingly, a recent comparison of the levels of charged tRNAs that carry the same amino acid (isoacceptors) relative to the nonrandom distributions of their corresponding codons in Escherichia coli genes suggested that the selective use of alternative isoacceptors can regulate certain functions (4).…”
mentioning
confidence: 99%
“…Although the level of expression of ccaR in S. clavuligerus was modest, the gylP1P2 promoter was nonetheless seen to be both active, and glycerol-regulated in S. clavuligerus. The presence of a TTA codon in ccaR may limit expression under the gylP1P2 promoter, although previous studies have shown that expression of ccaR is relatively insensitive to the availability of bldA tRNA in S. clavuligerus (Trepanier et al, 2002).…”
Section: Discussionmentioning
confidence: 88%
“…Unusually, the TTA-containing CSR gene ccaR for clavulanic acid/cephamycin C biosynthesis in S. clavuligerus is fully expressed in a bldA mutant (160,161). This is thought to indicate a context effect on the extent to which UUA codons are translatable in a bldA mutant, with UUA codons followed by G or A being more likely to be mistranslated in frame (160,161).…”
Section: A Special Regulatory Role For the Rare Leucine Codon Uua In mentioning
confidence: 99%
“…This is thought to indicate a context effect on the extent to which UUA codons are translatable in a bldA mutant, with UUA codons followed by G or A being more likely to be mistranslated in frame (160,161). Further analysis of this hypothesis is needed in order that the effects of TTA codons in antibiotic gene clusters can be reliably predicted.…”
Section: A Special Regulatory Role For the Rare Leucine Codon Uua In mentioning
confidence: 99%